Preliminary Investigation of Different Types of Inoculums and Substrate Preparation for Biohydrogen Production - Zainal B.S.; Zaini S.; Zinatizadeh A.A.; Mohd N.S.; Ibrahim S.; Ker P.J.; Mohamed H. (MDPI, 2024)
A pre-culture stage is required to obtain robustly-dividing cells with high hydrogen (H2) production capabilities. However, a step-by-step process for biohydrogen production is scarcely reported, mainly from palm oil wastewater. Therefore, this study developed a guideline to find the best inoculum heat treatment conditions and implement the selected conditions for biohydrogen production using palm oil wastewater. This study used raw palm oil mill effluent (POME) and POME sludge as substrate and inoculum, respectively. Our findings reveal that 80 C and 30 min were the best conditions for inoculum heat treatment. When testing the conditions on POME sludge and inoculating with raw POME (28 g COD/L) at 37 C (reaction temperature), 24 h (reaction time), and pH 5.5, 34 mL H2/d was recorded. A slight increase (1.1-fold) was observed compared to 5 g COD/L POME co-digested with 5 g/L glucose (31 mL H2/d). This discovery indicates that raw POME is a potential source for biohydrogen production under anaerobic fermentation and can be directly used as substrate up to 30 g COD/L. The proposed guideline could also be implemented for different organic wastes for biohydrogen production study. 2023 by the authors.